2020
DOI: 10.1007/s40195-020-01014-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact Toughness of Heat-Affected Zones of 11Cr Heat-Resistant Steels

Abstract: Aiming at the requirements of structural steel in Gen-IV nuclear reactor, the high-chromium martensitic heat-resistant steels containing 10-12% chromium were developed. The toughness of heat-affected zones (HAZs) is one of the important factors for evaluating the weldability of steels. In this paper, the simulated HAZs were fabricated using tempered SIMP steels. The effects of microstructures on the impact toughness of materials were analyzed using Vickers hardness tester, optical microscope, transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[ 43 ] The study suggested that the decrease of carbon content was beneficial to the toughness of HAZ. [ 44 ] Therefore, the C and Mn content of austenite in IC‐100% was lower and more homogeneous than the partially austenitized ICHAZs, resulting in the decline of the embrittlement of FM and GB (Figure 12a). Therefore, the grain refinement, high density of HAGBs, and the less embrittlement of microstructure improved the impact toughness of IC‐100% to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] The study suggested that the decrease of carbon content was beneficial to the toughness of HAZ. [ 44 ] Therefore, the C and Mn content of austenite in IC‐100% was lower and more homogeneous than the partially austenitized ICHAZs, resulting in the decline of the embrittlement of FM and GB (Figure 12a). Therefore, the grain refinement, high density of HAGBs, and the less embrittlement of microstructure improved the impact toughness of IC‐100% to some extent.…”
Section: Discussionmentioning
confidence: 99%